Ecological («Sustainable») Infrastructure as Realizable Basis for Sustainable Development - Alexander, Tetior (International Journal For Research In Agricultural And Food Science, 2016)
The concept of ecological («sustainable») infrastructure, which can become the basis for sustainable development, was created recently [3, 4]. Ecological infrastructure is a complex of urban, regional, global and cosmic, natural, manmade and natural-artificial objects and phenomena, which provide environmentally well-founded preservation environment of human life. It includes a system of knowledge, actions and decisions to maintain elasticity of socio-ecological system towns and countries, ecological education, conservation of living environment, promote ecological balance, reduce the negative impacts of human activities on the natural environment, with increased resource efficiency and consuming renewable resources, with a gradual transition to negentropy technology. A more realistic creatinghigh-quality ecological infrastructure and the living environment can replace poorly realizable concept of sustainable development.